Implementasi Komunikasi Internal Berbasis Kepemimpinan Transformasional di SMP Negeri 3 Purwakarta - Andi Iswandi; Aan Komariah; Abubakar Abubakar (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to describe and analyze the implementation of internal communication within the framework of the principal’s transformational leadership and its implications for teacher performance and participation at SMP Negeri 3 Purwakarta. This research employed a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, participant observation, and documentation involving the principal, vice principals, and teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The results of the study indicate that the principal implements an open, dialogical, and participative two-way communication pattern, which aligns with the dimensions of transformational leadership, particularly inspirational motivation, idealized influence, and individualized consideration. Effective internal communication is proven to enhance teachers’ work motivation, involvement in decision-making processes, and the development of a collaborative work culture within the school. In addition, the utilization of digital communication media supports the smooth flow of information and work coordination. The findings confirm that the success of transformational leadership is strongly influenced by the quality of internal communication that is built in a humanistic, open, and sustainable manner. Therefore, it is recommended that school principals continuously develop adaptive communication strategies, expand teacher participation in every school policy, and optimize the use of communication technology to improve the performance of educational organizations in a sustainable way. Keywords: transformational leadership, internal communication, teacher performance, school management, participation Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi komunikasi internal dalam bingkai kepemimpinan transformasional kepala sekolah serta implikasinya terhadap kinerja dan partisipasi guru di SMP Negeri 3 Purwakarta. Pendekatan yang digunakan adalah kualitatif dengan desain studi kasus deskriptif. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi terhadap kepala sekolah, wakil kepala sekolah, serta guru. Teknik analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan, dengan uji keabsahan menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan pola komunikasi dua arah yang terbuka, dialogis, dan partisipatif, yang selaras dengan dimensi kepemimpinan transformasional, khususnya pada aspek inspirational motivation, idealized influence, dan individualized consideration. Komunikasi internal yang efektif terbukti mampu meningkatkan motivasi kerja, keterlibatan guru dalam pengambilan keputusan, serta memperkuat budaya kerja kolaboratif di sekolah. Selain itu, pemanfaatan media komunikasi digital turut mendukung kelancaran arus informasi dan koordinasi kerja. Simpulan penelitian ini menegaskan bahwa keberhasilan kepemimpinan transformasional sangat dipengaruhi oleh kualitas komunikasi internal yang dibangun secara humanis, terbuka, dan berkelanjutan. Oleh karena itu, disarankan agar kepala sekolah terus mengembangkan strategi komunikasi yang adaptif terhadap perubahan, memperluas partisipasi guru dalam setiap kebijakan sekolah, serta mengoptimalkan pemanfaatan teknologi komunikasi untuk meningkatkan kinerja organisasi pendidikan secara berkelanjutan. Kata kunci: kepemimpinan transformasional, komunikasi internal, kinerja guru, manajemen sekolah, partisipasi guru